Framing Analysis of News Article about Clashes between Police and Terrorist Prisoners in Indonesia Publishing by ABC.net.au and SBS.com - Arbaiyah Satriani (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2018)
In 10 May 2018, six policemen had been killed in clashes between Indonesian police and prisoners in the jail in the Mobile Police Brigade (Brimob) headquarters in Depok, West Java. It was located in outskirts of Jakarta. The incident had attracted people’s attention from all around the world. One of the reasons was because it taken place in the headquarters of the police. It can be said as a dramatic tragedy. Another reason that it magnetized public’s awareness was because it involved so call terrorist prisoners. Two of online media that distributed news article about it in Australia were ABC and SBS new sites. Both of them are independent media and have difference focus of publication in their media. The aim of this paper is to explore how the two media, ABC and SBS new sites, frame the event in their publication. It is interesting to observe how the media in Australia which has special attention to the issues of Indonesia published the news article related to a hot topic in Indonesia